Predictors of Virologic Failure Among a Cohort of HIV-infected Children in Southern Ethiopia. Issue 1 (January 2021) - Tadesse, Birkneh Tilahun; Foster, Byron Alexander; Latour, Emile; Lim, Jeong Youn; Jerene, Degu; Ruff, Andrea; Aklillu, Eleni
Abstract : Background: Optimal care for children with HIV infection includes timely assessment of treatment failure. Using HIV viral load to define treatment failure remains a challenge in resource-limited settings. Methods: Children with HIV infection who were already on or starting first-line antiretroviral therapy were enrolled and followed over time. We examined clinical and immunologic predictors of virologic failure (VF), defined as consecutive viral load measurements > 1000 copies/mL (VF). Children were followed every 6 months with clinical assessments, immunologic assays and viral load testing until treatment failure or up to 18 months. Results: Of the 484 children with complete data, we observed a prevalence of 15% who had VF at enrollment, and 18 who developed VF over 10.5 person-years of follow-up for an incidence of 4.97 [95% CI: 3.04–7.70) per 100 person-years. Lower adherence, lower CD4 T-cell count, lower white blood cells count, lower platelets and a lower glomerular filtration rate were all associated with increased VF. However, in a multivariable analysis, renal function (estimated glomerular filtration rate < 90 mL/min), odds ratio: 11.5 (95% CI: 1.5–63.7), and lower adherence, odds ratio: 3.9 (95% CI: 1.1–13.4), were the only factors associated with development of VF. Conclusions: We identified a significant risk of VF in children with HIV infection in a prospective cohort study in southern Ethiopia and limited predictive value of clinical variables for VF. This provides further evidence that rapid and reliable viral load testing is needed to adequately address the HIV epidemic, along with implementation of adherence interventions in sub-Saharan Africa. Abstract : Supplemental Digital Content is available in the text.